The Impact Components of Banking Company Value consequence Corporate Social Responsibility (CSR), Intellectual Capital and Capital Structure - Dheanasti Habibatul Adawiyah; Tri Darma Rosmala Sari (Universitas Negeri Surabaya, 2025)
The objective of this investigation is to determine the impact of capital structure, intellectual capital, and corporate social responsibility on the value of banking companies listed on the Indonesian Stock Exchange during the period of 2021–2023. In this report, quantitative research was used. Researching specific groups or samples using quantitative methodologies yields tangible data, according to Sugiyono (2009). To evaluate established hypotheses, data collecting employs statistical data analysis and research instruments. The data source used is secondary data on banking companies in 2021-2023 from the website www.idx.co.id Muhlis & Gultom (2021Three independent variables—Corporate Social Responsibility (X1), Intellectual Capital (X2), and Capital Structure (X3)—as opposed to one dependent variable, Company Value (Y). According to the study's findings, capital structure has no discernible impact on company value, whereas intellectual capital has a major impact. Corporate social responsibility, on the other hand, has no discernible impact.